Work Stress, Risk Perception, and Social Support: Structural Equation Modeling of Healthcare Staffs’ Resilience - Xinran Huo; Yunke Shi; Ning Zhang (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2025)
The research aims to explore the current situation of resilience building of hospital medical personnel and its influencing factors, and try to put forward countermeasures and suggestions to improve the resilience of medical personnel, to alleviate the pressure of medical personnel’s work in normal times, and also to prepare for the effective enhancement of emergency treatment capacity in wartime. This study employed a cross-sectional design to survey medical staff from 2 hospital categories (infectious disease specialty hospitals and general hospitals). Using a stratified proportional sampling method, data were collected from 665 participants via scanned Wenjuanxing QR codes between January and March 2024. Data were analyzed using generalized linear models and structural equation modeling (SEM) to examine the relationships between resilience and its determinants. Significant differences in resilience levels were observed based on job position, title, income, and perceived occupational risk ( P  < .05). Social support emerged as a protective factor ( β  = .104, P  < .001), while risk perception ( β  = −.135, P  = .001) and work stress ( β  = −.195, P  < .001) negatively impacted resilience. Individual factors, such as age and job tenure, moderated these effects. The work stress of medical staff in municipal hospitals is close to the imbalance threshold, and the overall level of mental toughness is good, but attention needs to be paid to their mental health. Work stress, social support and risk perception play an independent role in influencing psychological resilience, with social support playing the highest role in the pathway relationship. We should take comprehensive measures from the welfare distribution system, supportive work environment, regular health promotion, psychological intervention management, and social care system to promote timely relief of work stress and effective mental health interventions for medical staff in municipal hospitals.